Muhammad bin Abdullah bin Abd al-Rahim al-Barqi, and His Book “Al- Tabakat”: (Examples of what was Quoted in the Book Al-Ikmaal, by Al-Hafiz Mugultai) - Al Muheiri, Kaltham Omar Al Majid (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: This research aims to introduce Ibn al-burqi Muhammad bin Abdullah bin Abdul Rahim and his critical efforts that did not get much luck from the study, as well as to reveal the importance of his lost book, "Al Tabakat", and to investigate its name. Methods: The study followed the descriptive approach; by collecting information related to Ibn al-burqi and his book, describing the importance of the criticism contained in it, and its characteristics, leading to a statement of the author's critical impact. Results: The study found that Ibn al-Barqi is one of the imams of criticism who are concerened with the conditions of prophetic Hadith narrators, and that his critical contributions stood out through his book "Al Tabakat", which is a precious book; in which he presented a summary of the judgments of critics in narrators, in precise words, with connotations that express the judgments of all critics. Conclusions: The need to follow up with the study on "Aldawa'afa" book to make use of it.